Комп’ютерне прогнозування гострої токсичності похідних 5-фенетил-4-R-3-тіо(аміно)-1,2,4-тріазолу завдяки GUSAR-online прогноза - Ігнатова, Т. В.; Фролова, Юлія Сергіївна; Каплаушенко, Андрій Григорович (My University, 2020)
An important step in the development of a new drug is the prediction of its toxicity by computer screening using the program GUSAR-online. The purpose of this work is an online prediction of acute toxicity among new derivatives of 5-phenethyl-4-R-3-thio(amino) 1,2,4-triazoles. Computer prediction of acute toxicity of 5-phenethyl-4-R-3-thio(amino)-1,2,4-triazole derivatives was performed according to the structural formulas of the compounds in the online version of the GUSAR-online program. GUSAR-online prediction for 5-phenethyl-4-R-3-thio(amino)-1,2,4-triazole derivatives was performed during the research. It was found that the average lethal dose of LD50 is from 56.1 to 2396.0 mg / kg. Based on this, all compounds are low-toxic and virtually non-toxic substances.
Keywords: 1,2,4-triazole; GUSAR-online; acute toxicity